Penerapan Terapi Rebusan Ekstrak Jahe Merah Dalam Menurunkan Kadar Kolestrol Pada Pasien Hiperkolesterolimia Dengan Teori Virginia Henderson Di Wilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu Tahun 2025 - Riska Maya Sari; Tita Septi Handayani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Hypercholesterolemia is an increase in total cholesterol or LDL cholesterol without an increase in triglyceride levels. Hypercholesterolemia is a condition characterized by elevated cholesterol levels >200 mg/dL and can be influenced by foods containing saturated fat or high in cholesterol. Normal total cholesterol levels in adult plasma are 120-200 mg/dL.The general objective of this case study is to apply Virginia Henderson's nursing theory to patients with hypercholesterolemia by performing and teaching the technique of administering boiled red ginger extract therapy. This research also aims to determine whether Virginia Henderson's theory can be applied to patients with hypercholesterolemia through the administration of boiled red ginger extract therapy.The results of nursing care for patients with hypercholesterolemia, by applying boiled red ginger extract therapy using Virginia Henderson's nursing theory, are conducted using the nursing process starting from the assessment process of 14 basic human needs, observation, and problem identification, nursing actions, nursing implementation, and nursing evaluation. The nursing interventions are structured to assist in lowering cholesterol levels through the boiled red ginger extract therapy technique with a Virginia Henderson approach.The Virginia Henderson nursing model theory can be applied effectively in nursing focused on cases of hypercholesterolemia. A recommendation for health workers is to apply the therapy of boiling red ginger extract in patients with hypercholesterolemia to lower cholesterol levels